2020
DOI: 10.1177/0047287520938875
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Environmentally Responsible Behavior for Tourists and Residents: A Norm Activation Theory Perspective

Abstract: Applying Norm Activation Theory to tourism, this study develops a conceptual model for both tourists and residents starting from their awareness of the negative environmental consequences of tourism, addressing ascription of responsibility, environmental sensitivity, place attachment, and environmentally responsible behavior. This research shows that ascription of responsibility mediates the relationship between awareness of negative consequences and that environmentally responsible behavior and environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 89 publications
(141 reference statements)
1
56
0
1
Order By: Relevance
“…Chen, Cottam, and Lin 2020). However, contrary to our own research, most of these studies adopt a resident (rather than a tourist) perspective, where the impact of tourism on citizens’ lives is explored (e.g., Bimonte et al 2019; Confente and Scarpi 2020; Nunkoo and Ramkissoon 2016). In these studies, it is also suggested that the impact of tourism on citizens can affect residents’ attitudes toward tourists at destinations, which plays an essential role in providing quality experiences for visitors.…”
Section: Theoretical Backgroundmentioning
confidence: 88%
See 1 more Smart Citation
“…Chen, Cottam, and Lin 2020). However, contrary to our own research, most of these studies adopt a resident (rather than a tourist) perspective, where the impact of tourism on citizens’ lives is explored (e.g., Bimonte et al 2019; Confente and Scarpi 2020; Nunkoo and Ramkissoon 2016). In these studies, it is also suggested that the impact of tourism on citizens can affect residents’ attitudes toward tourists at destinations, which plays an essential role in providing quality experiences for visitors.…”
Section: Theoretical Backgroundmentioning
confidence: 88%
“…Empirical evidence about the impact of interactions between local people and tourists on the travel experience is scarce in literature. However, some authors argue that in the same way that residents may have their daily lives enriched or degraded by the unending flow of tourists, tourists may likewise have their vacation spoiled or enhanced by residents (Bertella, Cavicchi, and Bentini 2018; Confente and Scarpi 2020; Knox 1982). Therefore, the local community plays a vital role at tourism destinations in providing quality experiences for tourists (Woosnam et al 2018).…”
Section: Research Model and Hypothesismentioning
confidence: 99%
“…We used an independent sample t-test to test hypotheses 1 and 2. We computed the mean scores of the goal commitment scale and goal-directed behaviors scale, respectively, and used the mean values in the independent samples t test (Confente and Scarpi 2020;Hair et al 2009;Ponsignon, Lunardo, and Michrafy 2020). The result showed that goal-directed behaviors of tourism goal disclosure were significantly higher than those of tourism goal nondisclosure (M disclosure = 5.96, SD = 0.49, vs. M nondisclosure = 5.31, SD = 1.31, t = 3.38, p < 0.01; see Figure 2); thus, hypothesis 1 was supported.…”
Section: Main Experimentsmentioning
confidence: 99%
“…A review of the literature shows that NAT has long been successfully used to investigate a wide variety of people’s intentions and behaviors such as travelers’ adoption behavior towards electric vehicles (Ashraf Javid et al 2021 ), environmentally responsible behavior for tourists and residents (Confente and Scarpi 2021 ), visitors’ binning behavior (Esfandiar et al 2021 ), farmers’ pro-environmental behavior in the face of drought (Hallaj et al 2021 ), organic food purchase intention (Le and Nguyen 2022 ), pro-environmental traveler behavior (O’Connor and Assaker 2021 ), farmers’ response to water crisis (Savari et al 2021 ), and compliance with COVID-19 prevention guidelines (Shanka and Gebremariam Kotecho 2021 ).…”
Section: Introductionmentioning
confidence: 99%